Feasibility of extracorporeal photopheresis in pediatric patients with graft‐versus‐host disease after hematopoietic stem cell transplantation. (11th April 2019) - Winther‐Jørgensen, Signe; Nygaard, Marietta; Heilmann, Carsten; Ifversen, Marianne; Sørensen, Kaspar; Müller, Klaus; Masmas, Tania
Abstract: Graft‐versus‐host disease (GVHD) is a main cause of morbidity and mortality following hematopoietic stem cell transplantation. The cumulative incidence of acute and chronic GVHD (aGVHD, cGVHD) reaches 30%‐50% and 20% in pediatric populations, respectively. Prednisolone and/or calcineurin inhibitors (CNI) are first‐line treatments, but no superior second‐line treatment has yet been established. Several treatments have been suggested, among others extracorporeal photopheresis (ECP). Technical advances have made treatment of pediatric patients possible; however, only few reports on the feasibility of ECP in children have been published. We retrospectively studied the feasibility, safety, and efficacy of ECP in 15 children with steroid‐dependent/refractory acute or chronic GVHD, who initiated ECP treatment between April 2014 and January 2018. Only few and mild side effects directly related to the ECP procedure were registered, even in patients with low body weight. The most frequent cause of shortened or canceled ECP treatment was difficulties with vascular accesses, which were more rarely seen using central venous catheters with larger lumens and made of stiffer material. Nine patients had grade II‐III aGVHD. Six of these experienced a response to ECP at day 28, while eight of nine had responded at the last ECP treatment. Six patients had cGVHD when ECP was initiated, and of these, four had a partial response at last ECP treatment. We found ECP to be a feasible and safe treatment, and particularly, children with aGVHD appeared to respond well to ECP.